Persepsi Siswa Terhadap Pelayanan Pegawai Perpustakaan di SMK Negeri 2 Payakumbuh - Clotilda Mori; Efrida Ita; Meo Maku, Karmelia Rosfinda; Dua Dhiu, Konstantinus (Global Action and Education for Society, 2024)
This research aims to improve reading literacy skills through planning and utilizing reading corners for grade IV students at SDK Nuabosi. This research was carried out at SDK Nuabosi, Ende Regency in 2024. This type of research is qualitative descriptive research. The subjects of this research were fourth grade students at SDK Nuabosi. The research method used for collection uses observation sheets, interviews and documentation. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results of the research show that the reading corner plays a very important role in growing and improving the reading skills of class IV students at SDK Nuabosi. With a reading corner, students can use the reading corner as a reading facility and also as a comfortable and attractive place to increase interest in reading. The reading corner is managed by teachers and students with the aim of introducing students to fun learning resources. Utilization of the reading corner in class IV of SDK Nuabosi as part of the school literacy movement (GLS), habit of reading 15 minutes before teaching and learning activities and also as reference and discussion material during learning activities.